PENGARUH PENGENDALIAN INTERNAL TERHADAP TAX AVOIDANCE DENGAN KEPEMILIKAN KELUARGA SEBAGAI VARIABEL MODERATING - Alya Dini Nabila Rachmawati; Abdul Rohman (Diponegoro Journal of Accounting, 2022)
This study aims to analyze empirically the effect of internal control on tax avoidance by using family ownership as a moderating variable. This analysis uses the independent variable, namely internal control. The dependent variable used in this study is tax avoidance. Family ownership was used as a moderating variable. Secondary data is used in the test with the research sample being manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019 with a total sample of 54 from 18 manufacturing companies. Sampling was done by purposive sampling. Hypothesis testing used in this research is multiple linear regression analysis and absolute value difference test for moderation assisted by SPSS computer program.The empirical results of this study prove that effective internal control has a negative effect on tax avoidance. Meanwhile, based on these results, it is also known that the existence of family ownership in the company does not moderate the relationship between internal control and tax avoidance.